Dynamics of Coach–Athlete Interpersonal Communication and Its Influence on Achievement Motivation in Woodball, A Case Study from Blora Regency Indonesia - Anugrah Ardannaga Pratama; Limpad Nurrachmad (Universitas Negeri Semarang, 2025)
The present study examines the dynamics of interpersonal communication between coaches and athletes and its influence on achievement motivation in the context of woodball, a developing sport in Indonesia. Employing a qualitative case study design, data were collected from 10 athletes and 2 coaches in Blora Regency through in-depth interviews, observations, and document reviews. The findings reveal that interpersonal communication—particularly openness, empathy, clarity, and supportiveness—has a substantial impact on enhancing athletes’ intrinsic and extrinsic motivation. The study also identifies challenges such as cultural hierarchies, limited communication training, and resource constraints that affect coach–athlete interactions. These findings underline the importance of communication competence in sports coaching, particularly in less mainstream sports where formal institutional support is limited. The paper concludes with recommendations for integrating interpersonal communication skills into coaching education and for further research on communication-driven athlete development in Indonesia.